Comparison of standard capillary electrophoresis based genotyping method and ForenSeq DNA Signature Prep kit (Illumina) on a set of challenging samples. (December 2017) - Votrubova, Jitka; Ambers, Angie; Budowle, Bruce; Vanek, D.
Abstract: DNA extracted from the challenging samples was analyzed with a standard capillary electrophoresis (CE) based genotyping method and with the ForenSeq™ DNA Signature Prep kit on the Illumina MiSeq FGx™ Forensic Genomics system. The results showed that more data can be obtained by MPS compared with CE with the same amount of input DNA and that use of MPS is influenced by the degree of damage of the template and amount of DNA available.